A Phase II Study of Stereotactic Body Radiation Therapy for Low-Intermediate-High-Risk Prostate Cancer Using Helical Tomotherapy: Dose-Volumetric Parameters Predicting Early Toxicity - Macias, Victor A.; Blanco, Manuel L.; Barrera, Inmaculada; Garcia, Rafael (Frontiers in Oncology, 2014)
Endpoint: To assess early urinary (GU) and rectal (GI) toxicities after helical tomotherapy Stereotactic Body Radiation Therapy (SBRT), and to determine their predictive factors. Methods: Since May 2012 forty-five prostate cancer patients were treated with 8 fractions of 5.48 (low risk, 29%) or 5.65 Gy (intermediate-high risk, 71%) on alternative days over 2.5 weeks. The exclusion criteria were: Gleason score 9-10, PSA >40 ng/mL, cT3b-4, IPSS ≥20 and history of acute urinary retention. During the follow-up a set of potential prognostic factors was correlated with urinary or rectal toxicity. Results: The median follow-up was 13.8 months (2-25 months). There were no grade ≥3 toxicities. Acute grade 2 GU complications were found in a 22.7% of men, but in 2.3% of patients at 1 month, 0% at 6 months and 0% at 12 months. The correspondent figures for grade 2 GI toxicities were: 20.4% (acute), 2.3% (1 month), 3.6% (6 months) and 5% (12 months). Acute GI toxicity was significantly correlated with the rectal volume (>15 cm3) receiving 28 Gy, only when expressed as absolute volume. The age (>72 years old) was a predictor of GI toxicity after 1 month of treatment. No correlation was found, however, between urinary toxicity and the other analyzed variables. IPSS increased significantly at the time of the last fraction and within the 1st month, returning to the baseline at 6th month. Urinary-related quality of life (IPSS question 8 score), it was not significantly worsen during radiotherapy returning to the baseline levels 1 month after the treatment. At 12 months follow-up patient’s perception of their urinary function improved significantly in comparison with the baseline. Conclusion: Our scheme of 8 fractions on alternative days delivered using helical tomotherapy is well tolerated. We recommend using actual volume instead of percentual volume in the treatment planning, and not to exceed 15 cm3 of rectal volume receiving ≥25 Gy in order to diminish acute GI toxicity.